Breaking bad. The complete third season - Cranston, Bryan, 1956-; Gunn, Anna, 1968-; Paul, Aaron, 1979-; Norris, Dean; Mitte, R. J.; Brandt, Betsy; Gilligan, Vince (Culver City, Calif. : Sony Pictures Home Entertainment, 2011)
Even though his cancer's in remission, chemistry teacher turned meth maker Walter White still can't catch a break. His wife has filed for divorce, his DEA agent brother-in-law is out to bust him, and a Mexican cartel just wants him dead. But with his family's future still at stake, Walt cooks up a deal that will make him a fortune, a scheme with a terrible price.
No mas -- Caballo sin nombre -- I.F.T. -- Green light -- Mas -- Sunset -- One minute -- I see you -- Kafkaesque -- Fly -- Abiquiu -- Half measures -- Full measure.
Features: cast and crew commentaries, deleted scenes and unused footage, gag reel, behind-the-scenes featurettes, mini video podcasts with the cast and crew on every episode, Better call Saul: commercials and testimonials, Inside "Breaking bad."
Bryan Cranston, Anna Gunn, Aaron Paul, Dean Norris, Betsy Brandt, RJ Mitte.
Originally broadcast on television in 2010.
TV rating: Not rated.
DVDs, Dolby digital 5.1 surround.
In English with optional French or Spanish subtitles; closed-captioned.
Keywords: Chemistry teachers -- Drama; Cancer -- Patients -- Drama; Drug dealers -- Drama; Chemistry -- Drama; Criminal behavior -- Drama; Drug traffic -- Drama; Terminally ill -- Drama; Crime -- Drama; Methamphetamine -- Economic aspects -- Drama; Drug dealers -- Family relationships -- Drama; Ice (Drug) -- Drama; Television crime shows; Fiction television programs; Television programs for the hearing impaired